Results of Tympanomastoid surgery in CSOM with Cholesteatoma (Attico-Antral Variety) - A study of 30 cases (Bangladesh Journal of Otorhinolaryngology, 2015)
In this prospective study 30 case of CSOM with cholesteotoma, admitted in 3 tertiary level hospitals, where modified radical mastoidectomy with type III tympanoplasty were done, then results of operation were assessed in follow up. The objectives of study to assess the clearance of disease, recurrence of disease and the cavity problem and to find the take rates of graft and improvement of hearing level after surgery. In this study most of the cases were younger age group (40%), male (60%), poorsocio- economic condition (73:33%), Illiterate (46.67%), day laborer (26.67%) & rural peoples (80%). It was observed that hearing status was improved 46.67%, unchanged 33.33% and deteriorated 20% cases. The mean, hearing gain was 10.79 dB. Also post mastoidectomy discharging ear was 20%, facial palsy 3.33%, recurrence of cholesteatoma 13.33%, dead ear 0%. Early detection and management of CSOM with cholesteatoma should be our goal to prevent complications. If good tympanomastoid surgery is done meticulously there will be improvement of hearing and less complications. DOI: http://dx.doi.org/10.3329/bjo.v20i1.22013 Bangladesh J Otorhinolaryngol; April 2014; 20(1): 20-26